Kepercayaan Konsumen Sebagai Mediasi Antara Sosial Media Marketing dan Viral Marketing Terhadap Keputusan Pembelian Pada Prime Video Indonesia - Parasari, Nyoman Sri Manik; Pratyahar, Kadek Yora (EconBank: Journal of Economics and Banking, 2024)
The development of the times accompanied by the development of information technology makes everything easier, including marketing. One way to attract consumers' attention and trust in their products is to use meme content as the content of choice that they post on their Twitter accounts so that consumers, especially their followers on Twitter, feel interested and increase curiosity, thereby giving rise to consideration when deciding to purchase their services. This research was conducted on Twitter social media, on the Prime Video Indonesia Twitter account. The population in this study is Twitter social media users in Indonesia, using a sampling technique in this study using a non-probability sampling technique with a sample size of 100 respondents. The method in this research uses quantitative analysis techniques using SEM-PLS mediation tests. The results of this research show that: (1) Social media marketing is proven to have a positive and significant effect on consumer trust, (2) Viral marketing is proven to have a positive and significant effect on consumer trust, (3) Consumer trust has a positive and significant effect on purchasing decisions. (4) Social media marketing has a positive and significant influence on purchasing decisions. (5) Viral marketing does not affect purchasing decisions. (6) social media marketing has a positive and significant effect on purchasing decisions through consumer trust. (7) viral marketing has a positive and significant influence on purchasing decisions through consumer trust.